THE NON-RETROACTIVITY OF NEW LEGAL NORMS - FUNDAMENTAL PRINCIPLE OF LAW. EXCEPTIONS - HEGHEȘ, Nicoleta-Elena (International Journal of Legal and Social Order, 2022)
The legal norm represents the internal structure of the law as a whole. The rule of law contains in its content the prescriptions to be followed, the rights and obligations of the subjects of law. All the social actions of our peers are placed in a normative framework, whether we are talking about law, morality, religion etc. The legal norm requires the acceptance and observance of the prescribed conduct. In this article, we have proposed to make a short analysis of the exceptions to the principle of non-retroactivity of legal norms, in particular the decriminalizing criminal norms and the criminal and contravention norms more favorable to the offender, respectively the contravenor; of interpretative legal norms; and express retroactivity.